2021
DOI: 10.21203/rs.3.rs-160848/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Pranayama and Deep Breathing Exercises to Reduce Cancer-Related Fatigue and Insomnia During Radiotherapy: A Randomized Controlled Study

Abstract: Background: Patients receiving radiotherapy often experience cancer-related fatigue and insomnia. These experiences negatively affect patients’ physiological and psychological well-being. The study aims to evaluate the effectiveness of pranayama and deep breathing exercise in reducing fatigue and insomnia in patients receiving radiotherapy due to breast cancer.Materials and methods: This randomized controlled interventional study was carried out with 60 patients divided into the pranayama (20), deep breathing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…This study showed that SDB and dhikr have a significant effect on sleep disturbance. This is by the study conducted by Gündogdu and Koçaşlı (2021), which proved that respiratory therapy has an effect on sleep disturbance in cancer patients experiencing chemotherapy. Mulhaeriah et al (2018), which examined the effectiveness of Relaxation Breathing Exercises (RBE) on fatigue FIMA 58 in cancer patients experiencing chemotherapy, stated that performing RBE 4 times a day for 7 days was more effective in alleviating fatigue than conducting RBE 2 times a day for 7 days.…”
Section: Discussionmentioning
confidence: 95%
“…This study showed that SDB and dhikr have a significant effect on sleep disturbance. This is by the study conducted by Gündogdu and Koçaşlı (2021), which proved that respiratory therapy has an effect on sleep disturbance in cancer patients experiencing chemotherapy. Mulhaeriah et al (2018), which examined the effectiveness of Relaxation Breathing Exercises (RBE) on fatigue FIMA 58 in cancer patients experiencing chemotherapy, stated that performing RBE 4 times a day for 7 days was more effective in alleviating fatigue than conducting RBE 2 times a day for 7 days.…”
Section: Discussionmentioning
confidence: 95%